FRI0263 Systemic disease activity progression in a large cohort of primary sjÖgren's syndrome: a long-term follow-up data based on the essdai score. (15th June 2017) - Quartuccio, L; Callegher, S Zandonella; Gandolfo, S; Fabro, C; Vita, S De
Abstract : Background: Primary Sjögren's syndrome (pSS) is a chronic slowly progressive autoimmune disease, which mainly affects the salivary and lachrymal gland function. However, it is an autoimmune systemic disease with a widespread spectrum of systemic manifestations, which are now captured by validated scores (1). Objectives: The aim of this restrospective study is to evaluate the disease course in a long-term follow-up, by focusing on the accrual of the systemic activity of the disease over time. Methods: 254 patients suffering from pSS were studied. Mean (standard deviation) age at diagnosis was 52 (13) years. They were 235/254 (92, 5%) females. Patients' chart were reviewed in order to compare the baseline ESSDAI score, ie calculated at the diagnosis, with the total ESSDAI accrual, by verifying the new onset ESSDAI domain and/or the worsening in already active ESSDAI domains in the whole available follow-up. Results: The observation covered 9, 1 (6, 9) years of follow-up from the diagnosis to the last follow-up visit. The median (range) baseline ESSDAI was 4 (0–31), while the total ESSDAI score accrual up to the last visit was 7 (0–43) (p<0, 0001, by Wilcoxon). The onset of new ESSDAI domains and/or worsening of already active ESSDAI domains was shown in 136/254 (53, 5%) patients, accounting for a total amount of 210 onsets of new domains or worsening in the already active domains [9, 1 (95% CI 5, 2–27, 7) events/100 patients/year]. There was no difference between patients with baseline ESSDAI score <5 and patients with baseline ESSDAI score ≥5 (56/103, 54, 4% vs 66/121, 54, 5%). In only 15/135 (11, 1%), the biologic domain was the sole ESSDAI domain, which was worsened or newly recorded. Finally, the ESSDAI domains, which more frequently raised or worsened in the follow-up were haematological (42/210, 20%), biological (37/210, 17, 6%), articular (37/210, 17, 6%), lymphadenopathy (28/210, 13, 3%), and peripheral nervous system (15/210, 7, 1%). Conclusions: Primary Sjögren's syndrome is not a benign disease, a half of patients showing an increasing disease activity, and probably damage, in terms of new onset or worsening of already existing manifestations, even when the disease activity is low at the onset. Importantly, clinically relevant changes over time are much more frequently observed than only biological changes, thus suggesting the need of a careful follow-up by experts, as well as the unmet need of effective treatments, according to disease activity and damage. References: Seror R, et al. Outcome measures for primary Sjögren's syndrome: a comprehensive review. J Autoimmun. 2014;51:51–6. Disclosure of Interest: None declared